Comparing the innovation performance of EU candidate countries: an entropy-based TOPSIS approach - Kaynak, Selahattin; Altuntas, Serkan; Dereli, Turkay (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
Innovation is important for countries in the competitive global economy. It is one of the main criteria for countries to be superior, to remain competitive, and to produce high technology products. Countries allocate different types of incentives to encourage innovation activities in their countries. Innovation is also one of the strategic issues for the European Union (EU). The aim of this study is to compare the innovation performance of four EU candidate countries, Macedonia (FYR), Iceland, Serbia and Turkey. The entropy-based Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) approach is proposed in this paper. First, the importance of each variable is computed by the entropy method to reflect on the differences among the variables in the calculation process. Subsequently, the TOPSIS method is performed by using the value and importance of variables for prioritisation of the candidate countries with respect to their innovation performance. Four case studies are conducted to show the viability of the proposed approach. Each cases study uses different reports, namely The Global Competitiveness Index, Innovation Union Scoreboard, Knowledge Assessment Methodology (KAM) and Global Innovation Index. The results of this study show that the proposed approach provides the same ranking as Innovation Union Scoreboard and KAM.
Keywords: Innovation; European Union (EU); candidate countries; entropy method; Technique for Order Performance by; Similarity to Ideal Solution (TOPSIS) method; ANALYTICAL NETWORK PROCESS; MANAGEMENT; KNOWLEDGE; WEIGHT; SYSTEM; POLICY; FYR; Business & Economics